104k views
0 votes
Maths question.
Solve
4(x - 1) = 2(6 - 2x)

User WilQu
by
5.4k points

2 Answers

5 votes
Use distributive property
4x - 4 = 12 - 4x
8x = 16
X = 2
User Dvanderb
by
4.8k points
6 votes

Answer:

x = 2

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

4(x - 1) = 2(6 - 2x)

Step 2: Solve for x

  1. Distribute: 4x - 4 = 12 - 4x
  2. Add 4x on both sides: 8x - 4 = 12
  3. Add 4 to both sides: 8x = 16
  4. Divide 8 on both sides: x = 2

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: 4(2 - 1) = 2(6 - 2(2))
  2. Multiply: 4(2 - 1) = 2(6 - 4)
  3. Subtract: 4(1) = 2(2)
  4. Multiply: 4 = 4

Here we see that 4 does indeed equal 4.

∴ x = 2 is a solution of the equation.

User Martin Ocando
by
5.1k points